2022
DOI: 10.1186/s13578-021-00740-z
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TCA cycle restrains virus-metabolic hijacking and viral replication in mouse hepatitis virus-infected cells

Abstract: Background One of coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused coronavirus disease 2019 (COVID-19) pandemic and threatened worldwide. However, therapy for COVID-19 has rarely been proven to possess specific efficacy. As the virus relies on host metabolism for its survival, several studies have reported metabolic intervention by SARS-CoV-2. Results We investigated the coronavirus-metabolic hijacking using mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Interestingly, in a subsample of the two cohorts (n=91), we found a positive correlation between circulating pyruvate levels measured by metabolomic and measured by fluorimetric analysis (R=0.551; P<0.001). With regards to the role of pyruvate in SARS-CoV-2 pathophysiology, it might have an anti-inflammatory function in macrophage activation, similar to the effect observed during influenza A virus infection ( 43 ), and it might also provide therapeutic benefit by suppressing viral replication through Krebs cycle induction ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a subsample of the two cohorts (n=91), we found a positive correlation between circulating pyruvate levels measured by metabolomic and measured by fluorimetric analysis (R=0.551; P<0.001). With regards to the role of pyruvate in SARS-CoV-2 pathophysiology, it might have an anti-inflammatory function in macrophage activation, similar to the effect observed during influenza A virus infection ( 43 ), and it might also provide therapeutic benefit by suppressing viral replication through Krebs cycle induction ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“… 168 Of note, mouse hepatitis virus infection model suggested that endogenous metabolites could alter mitochondrial metabolism and correspondingly modulate viral replication efficacy. 172 Thus, metabolic interventions may be employed to restrain mitochondria metabolism and SARS‐CoV‐2 replication. 172 , 173 It is worthy to mention that previous proteomic studies utilized overexpressed viral proteins as baits to track virus–host interaction.…”
Section: Mechanisms Of Remodeling Host Metabolism By Sars‐cov‐2mentioning
confidence: 99%
“… 172 Thus, metabolic interventions may be employed to restrain mitochondria metabolism and SARS‐CoV‐2 replication. 172 , 173 It is worthy to mention that previous proteomic studies utilized overexpressed viral proteins as baits to track virus–host interaction. 63 , 123 Further efforts are required to exclude potential experimental artifacts in physical association with mitochondrial enzymes.…”
Section: Mechanisms Of Remodeling Host Metabolism By Sars‐cov‐2mentioning
confidence: 99%
See 2 more Smart Citations